Atherosclerotic Risk Factors in Children with Celiac Disease. (27th March 2020) - Rybak, Anna; Wierzbicka, Aldona; Socha, Piotr; Stolarczyk, Anna; Cukrowska, Bożena; Obrycki, Łukasz; Wawer, Zbigniew; Janas, Roman; Oralewska, Beata; Szaflarska-Popławska, Anna; Iwańczak, Barbara; Cyrta-Jarocka, Elżbieta; et al.
Abstract : Introduction and Objectives . Celiac disease (CD) is a complex autoimmune disorder occurring in genetically susceptible individuals. There is limited data on the impact of gluten-free diet (GFD) on the risk of developing cardiovascular diseases. Hereby, we present our study regarding the impact of treatment with GFD on the biochemical risk factors of atherosclerosis. Material and Methods . 277 patients with CD from 7 Polish clinics were enrolled in the study (210 children treated for at least 5 years and 67 children included in the study on the day of CD diagnosis and observed for 1 year on a GFD). We obtained selected clinical data, and we assessed lipid profile, apolipoproteins (A1, B, and E), lipoprotein (a), homocysteine, as well as antioxidants (folic and uric acid), and high-sensitivity CRP (hsCRP) for all patients. The compliance to GFD was verified using anti-transglutaminase antibodies and deamidated gliadin peptide antibodies. As a reference group, the data of 95 healthy children recruited for another project was used, for which we had the results of selected parameters. Results . We found significantly lower concentrations of total cholesterol, lipoprotein LDL-C, apolipoproteins A1 and B, as well as hCRP in all children with CD. We showed decreased level (<5 ng/mL) of folic acid among 46% of children treated for >5 years. Moreover, we showed significant decrease of folic acid level already after 1 year of a GFD (12 vs . 5.6 ng/mL; p < 0.001 ). We also found significant negative correlation of z -score body mass index (BMI) with HDL and APOA1 level (r = − 0.33 ; p = 0.015 and r = − 0.28 ; p = 0.038, respectively) and modest positive correlation of z -score BMI with atherogenic factor of total cholesterol-HDL ratio and LDL-HDL ratio (r = 0.40 ; p = 0.002 and r = 0.36 ; p = 0.006, respectively). Analysis of physical activity showed an increase in the insulin levels with inactivity (r = 0.36 ; p = 0.0025 ). We also found positive correlation of the sleep duration with the adiponectin level (r = 0.41 ; p = 0.011 ). Conclusions . In children with CD treated with a GFD, decreased level of folic acid together with increased BMI, sedentary behavior, and an improper lipid profile may predispose them to atherosclerosis in the long run. This data suggests the need of further studies to determine the need for metabolic cardiovascular risk screening in children with CD.